The ecological effects of collecting Callianassa kraussi Stebbing and Upogebia africana (Ortmann) for bait : impacts on the biota of an intertidal sandflat - Wynberg, Rachel (Department of Biological Sciences, 2014)
Bibliography: leaves 122-142.